Manajemen Strategi Guru Menghadapi Kurikulum Merdeka di Sekolah Menengah Pertama - Damayanti, Alvina Dwi; Hasanah, Silviatul; Lestari, Prihatin (Universitas Pakuan, 2024)
The relationship between management as an important element in educational management with strategy as a way of implementing management has a close relationship. As a unified system, strategic management is indispensable in helping to implement an independent curriculum. The transformation of the implementation of the previous curriculum with the independent curriculum currently implemented by the government has quite specific developments. The use of technology, varied teaching materials and various methods that must be learned well by teachers today. This study aims to examine teachers' strategic management in dealing with the